Kinetic Analysis of Saponification Reaction in Eco-Friendly Soap Production Based on Waste Cooking Oil - Wahyudi, Apri; Sitrous, Berlian; Hidayat, Ferdinand (Hydrogen: Jurnal Kependidikan Kimia, 2025)
This study aims to determine the kinetics of the saponification reaction in making solid soap from wasted cooking oil and its effect on the quality of the solid soap produced. The novelty of this study lies in evaluates the effect of different NaOH concentrations and reaction durations on the the kinetic model with quality parameters (free fatty acid, free alkali content, and pH) to demonstrating that a pseudo second order reaction mechanism contributes to superior soap characteristics. The method begins with the refining of wasted cooking oil using activated carbon, making solid soap from refined oil with variations in NaOH concentrations of 1; 1.5; and 2 M in 30; 45; and 60 minutes. Determination of reaction kinetics was carried out by titrimetry and testing the quality of solid soap with parameters of free fatty acid content, free alkali, and degree of acidity (pH) based on SNI 3532-2021. The results showed that the saponification reaction followed 2nd order pseudo kinetics. This is supported by the value of the reaction constant reaching 1.0995 min-1 and the coefficient of determination R2= 0,9954. The optimum variation of solid soap obtained is 2 M NaOH concentration in 60 minutes. Soap products produced through pseudo second-order reaction kinetics have high quality with a white appearance, no rancid odor, smooth and soft texture. This is evidenced by the parameters of free fatty acid and free alkali content of 0.1126% and 0.016%. The degree of acidity (pH) of the solid soap produced is also in the range of 9.5-10. All of these parameters have met the criteria for solid soap according to SNI 3532: 2021.